Socialization of Pregnant Mother's Behavior on the Positive Culture Related to Pregnancy in the Tambaksari Village: Sosialisasi Perawatan Ibu Hamil Tentang Budaya Positif Berkaitan Kehamilan Di Desa Tambaksari Kabupaten Ciamis - Hindiarti, Yudita Ingga; Purnamasari, Kurniati Devi; Ningrum, Widya Maya (Jurnal Pengabdian Masyarakat Kesehatan Terkini, 2024)
Pregnancy care is a period of high urgency in which pregnancy is a critical phase of the condition for both the mother and the fetus. Most of the causes of maternal death are due to direct obstetric deaths from complications during pregnancy, bleeding, eclampsia, infection and low thrombocyte syndrome (HELLP) in primipara. Qualified and culturally safe maternal foster care plays an important role in improving the health of pregnant mothers. Unfortunately, there is currently little empirical evidence that proves that culture-based maternity foster care can play a role in attempting to reduce maternal mortality through effective fostering, namely the care of pregnant mothers. With regard to the objectives of socialization of maternal care, it is expected to increase the knowledge, awareness and positive attitude of mothers and families towards the care of pregnant mothers. The method used in the implementation of these activities through socialization or dissemination. As a result of this community service, there has been an improvement in the knowledge of pregnant mothers, where before being educated about the positive culture of health care, the majority of pregnancy mothers know less than 70% and the evaluation results after the implementation of the most pregnant women know well as 80%.